Evaluation of behaviour in stabled draught horse foals fed diets with two protein levels. (28th June 2016) - Sartori, C.; Guzzo, N.; Normando, S.; Bailoni, L.; Mantovani, R.
Abstract : The present work is aimed at evaluating the behaviour of Italian Heavy Draught Horse (IHDH) foals reared in semi-covered stables and fed two isoenergetic total mixed rations with different dietary protein levels (13.2% and 10.6% of CP on dry matter). The study was prompted by the restrictions for nitrate emissions in farms of the European Nitrate Directive. One suggested solution is to reduce dietary protein while maintaining normal performance and welfare, but there is a lack of literature in studies of horses. The behaviours of 20 foals of 437±60 kg of BW, aged 379±37 days and stabled in four pens by sex (S) and diet (D) were video recorded and analysed to build a suitable ethogram including 18 behaviours in six categories: ingestion, resting, maintenance, movement, social activities, other. The percentage of the daily time spent in each behavioural category and single behaviours was analysed via a single traits GLM including S, D and their interaction. Daily activity was consistent with existing literature: foals spent about 33% of the day in ingestion activities and 41% in resting, whereas social interactions constituted 8% of the time and individual maintenance <2%. Concerning diet, foals fed high protein spent more time in movement (19.62±0.73% of day v . 10.45±0.73% in low-protein (LP) foals; P ⩽0.001), whereas the LP group increased resting (43.42±1.12% v . 38.02±1.12%; P ⩽0.001). No stereotypies were found, and daily activity followed the typical values for draught breeds for foals in both dietary groups, a result that suggests the maintenance of well-being after dietary protein reduction. This result, together with the findings of a companion study showing no changes in growth performances of foals, showed that a reduction of CP in foal diet is reconcilable with the maintenance of performance and welfare.